Behavior of Lutung Budeng (Trachypithecus auratus) in Adinuso Forest Batang District Central Java - Rizki Fitrawan Yuneldi; Fibria Kaswinarni (Biotropika: Journal of Tropical Biology, 2021)
Lutung Budeng (Trachypithecus auratus) is an endemic primate of Indonesia, especially Java, Bali, and Lombok, which is vulnerable. This study aimed to determine the behavior of Lutung Budeng in the Adinuso Subah forest, Batang Regency. The study was conducted from January to December 2019. Lutung Budeng behavior is observed directly in the field using the roaming or exploration method. The equipment used were the digital singlelens reflex camera of the Canon EOS 650 D, telephoto tamron 70-300 mm, tripod, Sony handycam HRD- PJ410, compass, and Nikon Binocular A211 16x50 mm. The recorded vocal of Lutung Budeng was analyzed using Audacity. The data observed were the behavior of moving places, feeding, grooming, resting, playing, and vocalization. The data obtained were analyzed by means of descriptive qualitative. The results showed that in the Adinuso forest, the feeding behavior of Lutung Budeng did not interact with visitors or humans to get feed. Lutung Budeng more often feeds young leaves. It can be concluded that the behavior of Lutung Budeng in Adinuso Subah forest, Batang Regency is relatively the same as the behavior of Lutung Budeng in general. The behavior of Lutung Budeng in the Adinuso forest includes moving places, feeding, resting, grooming, vocalization, and playing.